Performance, Rumen Microbial Community and Immune Status of Goat Kids Fed Leucaena leucocephala Post-weaning as Affected by Prenatal and Early Life Nutritional Interventions - Artiles-Ortega, Einar; Portal, Orelvis; Jeyanathan, Jeyamalar; Reguera-Barreto, Beydis; de la Fé-Rodríguez, Pedro Yoelvys; Lima-Orozco, Raciel; Fievez, Veerle (Frontiers in Microbiology, 2022)
Leucaena leucocephala represents a local protein source in tropical ruminant diets. However, its full exploitation is impaired by mimosine, unless it is degraded by the rumen microbial community. Recently, the ruminal bacterial communities of newborns were persistently modified through prenatal or postnatal dietary interventions. Such early-life interventions might enhance adaptation of ruminants to Leucaena leucocephala, which was investigated (2x2 factorial design) by the inclusion of L. leucocephala in the late pregnancy diet and/or supplementation of live yeast to newborns. The composition of ruminal bacteria, immune status, as well as organic matter digestibility (OMD) and performance of kids were studied during and after the intervention. Ten pregnant goats were divided into two groups: the D+ and D- group, either or not receiving 30 g of L. leucocephala forage meal during the last 7±0.5 weeks of gestation. Twins from each goat were divided into the K+ and K- groups (either or not receiving 0.2 g/d of live yeast from day 3 until weaning at 8 weeks). Rumen samples were collected from 4-, 8-, 14- and 20-weeks old kids to assess the bacterial community, while immune parameters (white blood cells, immunoglobulin M and G, and chitotriosidase activity) were measured in blood and saliva sampled at 4-, 8- and 20-weeks. We found a stimulatory effect of the prenatal exposure on the post-weaning dry matter intake of the L. leucocephala supplemented diet, resulting in a higher daily gain and final body weight at 20 weeks in the D+ vs. D- group (406 vs. 370 g DM/d, 85.4 vs. 78.6 g/d and 15.2 vs. 13.8 kg, respectively). Moreover, Ruminococcus represented a greater proportion of the rumen bacterial community of the D+ vs. D- kids (5.1 vs. 1.6 %). Differences in the immune status were relatively small and not thought to be a driving factor of differences in animal performance. Furthermore, postnatal supplementation of live yeast favored maturation of the rumen bacterial community (i.e. greater importance of Bacteroidetes, in particular Prevotella, and reduced abundance of Firmicutes) and protozoa colonization. Concomitantly, OMD was enhanced post-weaning, suggesting effects of the early-life intervention persisted and could have affected animal performance.